A Study on MDA5 Signaling in Splenic B Cells from an Imiquimod-Induced Lupus Mouse Model with Proteomics - Yu-Jih Su; Fu-An Li; Jim Jinn-Chyuan Sheu; Sung-Chou Li; Shao-Wen Weng; Feng-Chih Shen; Yen-Hsiang Chang; Huan-Yuan Chen; Chia-Wei Liou; Tsu-Kung Lin; Jiin-Haur Chuang; Pei-Wen Wang (Cells, 2022)
Introduction: Several environmental stimuli may influence lupus, particularly viral infections. In this study, we used an imiquimod-induced lupus mouse model focused on the TLR7 pathway and proteomics analysis to determine the specific pathway related to viral infection and the related protein expressions in splenic B cells to obtain insight into B-cell responses to viral infection in the lupus model. Materials and Methods: We treated FVB/N wild-type mice with imiquimod for 8 weeks to induce lupus symptoms and signs, retrieved splenocytes, selected B cells, and conducted the proteomic analysis. The B cells were co-cultured with CD40L+ feeder cells for another week before performing Western blot analysis. Panther pathway analysis was used to disclose the pathways activated and the protein–protein interactome was analyzed by the STRING database in this lupus murine model. Results: The lupus model was well established and well demonstrated with serology evidence and pathology proof of lupus-mimicking organ damage. Proteomics data of splenic B cells revealed that the most important activated pathways (fold enrichment > 100) demonstrated positive regulation of the MDA5 signaling pathway, negative regulation of IP-10 production, negative regulation of chemokine (C-X-C motif) ligand 2 production, and positive regulation of the RIG-I signaling pathway. A unique protein–protein interactome containing 10 genes was discovered, within which ISG15, IFIH1, IFIT1, DDX60, and DHX58 were demonstrated to be downstream effectors of MDA5 signaling. Finally, we found B-cell intracellular cytosolic proteins via Western blot experiment and continued to observe MDA5-related pathway activation. Conclusion: In this experiment, we confirmed that the B cells in the lupus murine model focusing on the TLR7 pathway were activated through the MDA5 signaling pathway, an important RNA sensor implicated in the detection of viral infections and autoimmunity. The MDA5 agonist/antagonist RNAs and the detailed molecular interactions within B cells are worthy of further investigation for lupus therapy.